Wildfires, Fire Management, and Optimal Land Carbon Policy - Elder, Molly. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Economics.; Advisor: Jeffrey Zabel.; Committee: Gilbert Metcalf, Brendan Rogers, and Shinsuke Tanaka.; Keyword: Environmental economics.